The Antecedents of Slow Fashion Product Purchase Decision Among Youth in Bandung, Jakarta, and Surabaya - Aldilax, Dandy; Hermawan, Pri; Mayangsari, Lidia (KnE Social Sciences, 2020)
The global trend of apparel industry is having positive correlation with Indonesia fashion retail trend. Recently, there has been growing in awareness among Indonesia consumer about environment make slow fashion product become more popular. However, there are lack of empirical evidence about Indonesian consumers’ slow fashion purchase decision and environment-friendly attitudes. This research aim to investigate the influencing factor of slow fashion product purchase decision among Indonesian youth. Based on the result, researcher can determine influencing factor of slow fashion product purchase decision. This research used quantitative approach through questionnaire with total 250 respondents ranging age 18-24 in 3 major cities in Indonesia which is Bandung, Jakarta, and Surabaya. In investigating the influencing factors, researcher gain four hypothesis from literature review. The factor tested in this research are personal environmental norms, past environmental friendly behaviour, green marketing, and peer influence in green context. The result of the study shows only peer influence in green context has significant correlation to slow fashion product purchase decision. This study is important to understand customer behaviour in slow fashion product and help marketer to find right marketing strategy. Keywords: Purchase Decision; Slow Fashion; Indonesian Youth; Green Behavior; Environmental Friendly Attitudes